Synthesis of Methyl Ester from Waste Cooking Oil Toward Application in Transformer’s Insulating Liquid - Dung, Nguyen Van; Thi, Nguyen Thi Xuan; Truong, Le Vinh (VNU Journal of Science: Natural Sciences and Technology, 2023)
This study evaluated the feasibility of using methyl ester prepared from waste cooking oil for electrical insulation in distribution transformers. Methyl ester is produced by a transesterification reaction between waste cooking oil and methanol using sodium hydroxide as a catalyst. The physicochemical parameters and breakdown voltage of the methyl ester were determined. The effects of ageing on breakdown voltage, viscosity and acid value of methyl ester were also investigated. In addition, the breakdown voltage of Kraft paper impregnated with methyl ester was determined. Experimental results showed that methyl ester from waste cooking oil had low viscosity (5.17 cSt) and high breakdown voltage (40.3 kV). Other parameters also meet ASTM D6871 except for the pour and flash points. Ageing insignificantly affected the breakdown voltage of the methyl ester. After ageing, the breakdown voltage of the methyl ester increased to 42.1 kV. However, the viscosity of the methyl ester also increased by 23.5% and the acid value increased by 79.2 times. Finally, the breakdown voltage of Kraft paper impregnated with the methyl ester was about 5-10% lower than that of paper impregnated with the mineral oil.